Water and Reinforced Effects on Slope: Case Study on District Koto Panjang, Riau, Indonesia - Nugroho, Soewignjo Agus; Yusa, Muhamad; Sujatmoko, Bambang; Ongko, Andarsin (Journal of Geoscience, Engineering, Environment, and Technology, 2024)
This paper discussed a study case related to slope stability and its analysis. The observation and also research object was a hill side on border area between West Sumatera-Riau, Indonesia. This border area consists of numerous slopes with heterogeneous soil characteristics. This location is also susceptible for having landslides, especially on rainy season. The schemes of this research consisted of collecting samples, laboratory tests, finite element method analysis, and slope`s reinforcement planning with anchors or geosynthetic plates. The soil samples were tested on their actual condition and liquid limit condition. This purposed to predict the failures on slope. Afterwards, some reinforcement plannings need to be done. The results of this researach have shown that on existing condition, the safety factor was 1.262. If the soil reach its liquid limit, the safety factor decreased to 0.568. After the reinforcement planning was done, the safety factor went up to 1.120 and the slope stability could be maintained.